2015
DOI: 10.7314/apjcp.2015.16.7.2731
|View full text |Cite
|
Sign up to set email alerts
|

Public Awareness of Warning Signs and Symptoms of Cancer in Oman: A Community-Based Survey of Adults

Abstract: Background: The majority of deaths from cancer occur in low and middle income countries, partly due to poor public awareness of the signs and symptoms of cancer. Materials and Methods: A community based survey using the Cancer Awareness Measure (CAM) questionnaire was conducted in three different communities in Oman. Omani adults aged 18 years and above were invited to participate in the study. Results: A total of 345 responded from 450 invited participants (response rate=76.7%). The majority of respondents we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
26
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 35 publications
6
26
1
Order By: Relevance
“…It is well known that education is very important for good health. This finding is supported by other studies, indicating that education is an important marker in healthy behavior [1,2,8].…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…It is well known that education is very important for good health. This finding is supported by other studies, indicating that education is an important marker in healthy behavior [1,2,8].…”
Section: Discussionsupporting
confidence: 90%
“…This finding is supported by an Omani study in which respondents showed a low awareness about eating less fruit and vegetables, and where obesity and the eating of red or processed meat were associated with cancer risk [2]. With this reduced awareness, there is a high risk of Nepali people suffering from cancer.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…The internal reliability and test-retest reliability of CAM questionnaire was found to be high ). The CAM questionnaire was translated from English to Arabic and back-translated into English again by several people proficient in both languages, and the Arabic version of the CAM questionnaire has been used in previous studies conducted among adults in Oman (Al-Azri et al, 2014;Al-Azri et al. 2015;Al-Azri et al, 2016).…”
Section: Tool Used To Measure Cancer Awarenessmentioning
confidence: 99%